Dual-mode robust fault estimation for switched linear systems with state jumps. (February 2018) - Johnson, Scott C.; Chakrabarty, Ankush; Hu, Jianghai; Żak, Stanisław H.; DeCarlo, Raymond A.
Abstract: Fault detection and estimation is a critical part of modern control system design and ensures safety and reliability of expensive machinery. In this paper, a dual-mode state and fault estimation scheme is proposed for switched linear systems with a class of state jumps in the presence of simultaneous actuator and sensor faults. In the absence of sensor faults, a switched sliding mode observer is developed to estimate the state and actuator fault signal. A residual signal is computed to detect the inception of a sensor fault. Upon detecting the sensor fault, a robust state observer is triggered which guarantees ultimate boundedness of the state estimation error. The performance of the proposed dual-mode switched observer is illustrated using a numerical example.